Policy Analysis in Canada - Howlett, Michael, 1955-; Laycock, David H., 1954-; Dobuzinskis, Laurent (Book collections on Project MUSE., 2007)
"Offers a comprehensive overview of the many ways in which the policy analysis movement has been conducted, and to what effect, in Canadian governments and, for the first time, in business associations, labour unions, universities, and other non-governmental organizations."--Publisher